Evaluation of the Mechanical Failure Criterion to Consider the Triple Base Propellant Safety Life: Application of Sustainable Renewables for Environmental Hazards - Liqian Song; Yan Wang; Dabin Liu; Hua Qian; Xiaoting Rui; M. Mehdi Shafieezadeh (Discrete Dynamics in Nature and Society)
Implementation of clean energy and renewables is essential for the consideration of environmental impact because it can be implemented in supply chain networks and sustainable management procedures for safety. In order to study the safety life failure criterion of a triple base propellant under the failure mode of mechanical properties, an accelerated aging test, an evaluation method for the launch safety test of gun propellant charge, and a compressive strength test were used. The failure criterion of mechanical properties was obtained by researching the correlation between launch safety change and mechanical property change of samples. Berthelot’s equation was used to predict the safety life of the triple base propellant. The results show that the mechanical failure criterion is “27% reduction of maximum compressive strength.” The safety life at 25°C and 75% humidity is 13.77 years.